Internal Debt Options during the Two Double Shocks and Its Impact on Foreign Reserve in Iraq - Lafta, Hasan Hazim; Jawad , Saja Fadhil (Journal of Economics and Administrative Sciences, 2022)
The research aims at a statement Internal Debt options during shocks and the impact of this borrowing in the volume of the foreign reserve, using induction and deduction with available data analysis. During the period (2004-2013) did not require the use of borrowing across (financial institutions, discounted transfers, bonds); it was only sufficient by transfer with commercial banks that can finance of temporary budget deficits: rose and decline of volume of foreign reserve according to the changes of oil prices and the volume of purchases and sales of the Central Bank of Iraq. Central Bank of Iraq (CBI) has significantly contributed to Internal Debt through bond and discounted transfers in the secondary market; thus, funding the public budget and sustaining the momentum of battles during the first double shock (2014-2017), which reflected how it is negatively affected the volume of foreign reserve, in other words, reduction the proportion of foreign assets to local assets. The second double crisis (2020) reduced the exchange rate of the Iraqi dinar against the US dollar, which was reflected at high prices; inflation reached (5.6) at the end of the first half of 2020, which means adopting a new choice to finance the budget deficit. This means that there is an inverse relationship between the volume of foreign reserve and internal debt, where decrease volume of foreign reserve during two double shocks